2022
DOI: 10.1186/s40824-021-00248-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcrystalline growth of PLLA on carbon fiber grafted with nano-SiO 2 towards boosting interfacial bonding in bone scaffold

Abstract: Background The reinforcement effect of fiber-reinforced polymer composites is usually limited because of the poor interfacial interaction between fiber and polymer, though fiber reinforcement is regarded as an effective method to enhance the mechanical properties of polymer. Methods In this study, nano-SiO2 particles grafted by 3-Glycidoxypropyltrimethoxysilane (KH560) were introduced onto the surface of 3-Aminopropyltriethoxysilane (KH550) modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…In the FTIR spectrum (Fig. 3 g), the absorption peak at 1076 cm −1 in Fe 3 O 4 @SiO 2 was adscripted to Si–O bond while the peak at 592 cm −1 was attributed to Fe–O bond [ 28 30 ], which further confirmed that the core–shell structure of Fe 3 O 4 @SiO 2 nanochains.…”
Section: Resultsmentioning
confidence: 66%
“…In the FTIR spectrum (Fig. 3 g), the absorption peak at 1076 cm −1 in Fe 3 O 4 @SiO 2 was adscripted to Si–O bond while the peak at 592 cm −1 was attributed to Fe–O bond [ 28 30 ], which further confirmed that the core–shell structure of Fe 3 O 4 @SiO 2 nanochains.…”
Section: Resultsmentioning
confidence: 66%
“…In the FTIR spectrum (Fig. 3g), the absorption peak at 1076 cm − 1 in Fe 3 O 4 @SiO 2 was adscripted to Si-O bond while the peak at 592 cm − 1 was attributed to Fe-O bond [29][30][31], which further con rmed that the coreshell structure of Fe 3 O 4 @SiO 2 nanochains.…”
Section: Fe 3 O 4 @Sio 2 Nanochainsmentioning
confidence: 72%
“…42 Specifically, during the cooling process, the nanoparticles with a large specific surface area and high surface activity could act as nucleating sites to induce the ordered arrangement of polymer chain under a higher temperature. 43,44 Furthermore, it was found that the sintering window, defined as the difference between the melting temperature and crystallization temperature, was enlarged with the introduction of nanoparticles. It had been reported that the larger the sintering window, the more conducive to processing.…”
Section: Resultsmentioning
confidence: 99%